Fear of failure and Entrepreneurial intentions in University Students - Mutmainnah Mutmainnah; Ismarli Muis; Andi Nasrawaty Hamid (Journal of Educational, Health and Community Psychology, 2024)
This study aimed to investigate the relationship between fear of failure and entrepreneurial intentions in students. The Entrepreneurial Intention Questionnaire (EIQ) was used to assess entrepreneurial intention, while the Performance Failure Appraisal Inventory (PFAI) was employed to evaluate the fear of failure. The study involved 288 students from various regions in Indonesia, and accidental sampling was used as the sampling technique. The analysis, using the Spearman-Rho correlation test, revealed a negative correlation between fear of failure and entrepreneurial intention (p = 0.033 (p < 0.05)), indicating that higher levels of fear of failure were associated with lower entrepreneurial intentions. Furthermore, the analysis showed that specific aspects of fear of failure, such as fear of shame and embarrassment (p = 0.016), fear of devaluing one's self-estimate (p = 0.002), and fear of having an uncertain future (p = 0.031) were significantly negatively correlated with entrepreneurial intentions. However, the fear of important others losing interest and the fear of upsetting important others showed no correlation with entrepreneurial intention. Additional analysis revealed no significant differences in entrepreneurial intention based on age and gender, but a significant difference was observed based on domicile. Fear of failure also did not show significant differences based on the age, gender, and domicile of the respondents.